A study of porous carbon structures derived from composite of cross-linked polymers and reduced graphene oxide for supercapacitor applications. (July 2022) - Bakhoum, Daba T.; Oyedotun, Kabir O.; Sarr, Samba; Sylla, Ndeye F.; Maphiri, Vusani M.; Ndiaye, Ndeye M.; Ngom, Balla D.; Manyala, Ncholu
Abstract: In this study, hydrothermal and chemical vapor deposition (CVD) methods were used to prepare cross-linked polymer-based porous carbonaceous materials designated as activated carbon from polyvinyl alcohol (AC-PVA), activated carbon from polyvinyl alcohol/reduced graphene (AC-PVA/rGO) and activated carbon from polyvinyl alcohol/reduced graphene/polyvinyl pyrrolidone (AC-PVA/rGO/PVP). The structural properties of the as-prepared samples indicated a higher degree amorphicity. The textural analysis revealed high specific surface areas along with high void fractions for the samples. The electrochemical analysis of the cross-linked polymer-based activated carbons conducted as three-electrodes revealed the samples' potential as electrode materials for supercapacitors' applications. Activated carbon from PVA/rGO/PVP exhibited a superior specific capacitance (223 F g −1 ), a smaller charge transfer resistance (RCT = 1.0 Ω) and equivalent series resistance (ESR = 0.54 Ω) as compared to AC-PVA and AC-PVA/rGO. Remarkably, a fabricated symmetric device based on the AC-PVA/rGO/PVP as electrode and designated as AC-PVA/rGO/PVP//AC-PVA/rGO/PVP, delivered a high specific energy of 19.5 W h kg −1 corresponding to a specific power of 400 W kg −1 at 0.5 A g −1 . Besides, the supercapacitor displayed a stable evolution of capacitance, high coulombic efficiency of 99.8% and good related capacitance retention of 82.3% during a 10, 000 galvanostatic charge/discharge cycles conducted for the device in an extended cell potential of 1.6 V at 5.0 A g −1 in 2.5 mol L −1 KNO3 aqueous electrolyte. These encouraging results demonstrate the versatile potential of the carbon materials for future electrochemical energy storage devices. Graphical abstract: Unlabelled Image Highlights: Porous carbons from cross-linked polymers and reduced graphene oxide is prepared via hydrothermal and activation A synergy of features is achieved by cross-linking of polyvinyl alcohol and polyvinyl pyrrolidone AC-PVA/rGO/PVP displayed high electrochemical performance The device recorded specific energy and power of 19.5 W h kg −1 and 400 W kg −1 respectively in 2.5 M KNO3 electrolyte